READINESS OF THE FUTURE TEACHER FOR INNOVATIVE ACTIVITIES - Mykolaiko, V.P.; Mykolaiko І. (SWorld-Ger Conference proceedings, 2023)
The article substantiates the essence and content of future teacher’s readiness for innovative activity in higher pedagogical school. Contemporary requirements for the professional training of future teachers are presented in the context of the future tea